Antioxidant and Anti-inflammatory Extracts From Sea Cucumbers and Tunicates Induce a Pro-osteogenic Effect in Zebrafish Larvae - Carletti, Alessio; Cardoso, Carlos; Lobo-Arteaga, Jorge; Sales, Sabrina; Juliao, Diana; Ferreira, Inês; Chainho, Paula; Dionísio, Maria Ana; Gaudêncio, Maria J.; Afonso, Cláudia; Lourenço, Helena; Cancela, M. Leonor; et al. (Frontiers in Nutrition, 2022)
Bone metabolic disorders such as osteoporosis are characterized by the loss of mineral from the bone tissue leading to its structural weakening and increased susceptibility to fractures. A growing body of evidence suggests that inflammation and oxidative stress play an important role in the pathophysiological processes involved in the rise of these conditions. As the currently available therapeutic strategies are often characterized by toxic effects associated with their long-term use, natural antioxidants and anti-inflammatory compounds such as polyphenols promise to be a valuable alternative for the prevention and treatment of these disorders. In this scope, the marine environment is becoming an important source of bioactive compounds with potential pharmacological applications. Here, we explored the bioactive potential of three species of holothurians (Echinodermata) and four species of tunicates (Chordata) as sources of anti-oxidant and anti-inflammatory compounds with a particular focus on polyphenolic substances. Hydroethanolic and aqueous extracts were obtained from animals’ biomass and screened for their content of polyphenols and their antioxidant (DPPH, ATBS, FRAP) and anti-inflammatory properties (COX-2 inhibition). Hydroethanolic fractions of three species of tunicates belonging to the Family Polyclinidae displayed high polyphenolic content associated with strong antioxidant potential and anti-inflammatory activity. Extracts were thereafter tested for their capacity to promote bone formation and mineralization by applying an assay that uses the developing operculum of zebrafish (Danio rerio) to assess the osteogenic activity of compounds. The same three hydroethanolic fractions from tunicates were characterized by a strong in vivo osteogenic activity, which positively correlated with their anti-inflammatory potential as measured by COX-2 inhibition. This study highlights the therapeutic potential of polyphenol-rich hydroethanolic extracts obtained from three species of tunicates belonging to the Family Polyclinidae as a substrate for the development of novel drugs for the treatment of bone disorders correlated to oxidative stress and inflammatory processes.